Wedding People - Alison Espach (London Phoenix, 2025)
The smash-hit international bestseller A Read With Jenna book club pick Winner of the Goodreads Choice Award for Fiction 'Best read of the year' THE TIMES 'Books as fun as this one are few and far between' GUARDIAN 'Sharp, funny and a joy to read' OBSERVER Phoebe Stone arrives at a grand beachside hotel in Rhode Island wearing her best dress and least comfortable shoes. Immediately she is mistaken for one of the wedding people - but she's actually the only guest at the Cornwall Inn who isn't here for the big event. When the bride discovers her elaborate destination wedding could be ruined by a divorced and depressed stranger, she is furious. Lila has spent months accounting for every detail and every possible disaster - except for, well, Phoebe . . . Soon, both women find their best-laid plans derailed and an unlikely confidante in one another. Hilarious and moving, The Wedding People is an irresistible novel about love, friendship, dysfunctional families, and the unexpected paths that lead to happiness. 'As soon as I'd finished it, I wanted to read it all over again' RED 'Laugh-out-loud funny and surprisingly moving' INDEPENDENT 'So funny and romantic . . . A perfect novel' CATHERINE NEWMAN 'Glorious . . . made me wish I had written it' JOJO MOYES 'Utterly charming . . . I loved it' PANDORA SYKES 'One of the few weddings I've attended that I didn't want to end' SAMUEL BURR
Keywords: English Fiction